Diagnosis and management of infertility: NICE-adapted guidelines from the Italian Society of Human Reproduction - Stefano Palomba; Paola Viganò; Sandrine Chamayou; Zaira Donarelli; Maria Paola Costantini; Roberto Marci; Paola Piomboni; Egidio Fino; Luigi Montano; Antonino Guglielmino; Edgardo Somigliana; and the SIRU Working Group on Italian Guideline for Infertility (BMC, 2024)
Abstract In Italy the fertility rate is very low, and an increasing number of patients are infertile and require treatments. The Italian Law concerning the safety of patient care, and the professional liability of health professionals, indicates that health professionals must comply with the recommendations set out in the guidelines developed by public and private bodies and institutions, as well as scientific societies and technical-scientific associations of the health professions, except for specific cases. Unfortunately, no guideline for the diagnosis and the management of infertility is currently available in Italy. In 2019, the Italian Society of Human Reproduction pointed out the need to produce Italian guidelines and subsequently approved the establishment of a multidisciplinary and multiprofessional working group (MMWG) to develop such a guideline. The MMWG was representative of 5 scientific societies, one national federation of professional orders, 3 citizens' and patients' associations, 5 professions (including lawyer, biologist, doctor, midwife, and psychologist), and 3 medical specialties (including medical genetics, obstetrics and gynecology, and urology). The MMWG chose to adapt a high-quality guideline to the Italian context instead of developing one from scratch. Using the Italian version of the Appraisal of Guidelines for Research and Evaluation II scoring system, the National Institute of Clinical Excellence guidelines were selected and adapted to the Italian context. The document was improved upon by incorporating comments and suggestions where needed. This study presents the process of adaptation and discusses the pros and cons of the often-neglected choice of adapting rather than developing new guidelines.